Mammary gland responses to altering the supply of de novo fatty acid substrates and preformed fatty acids on the yields of milk components and milk fatty acids - A.C. Benoit; J.M. dos Santos Neto; A.L. Lock (Journal of Dairy Science, 2024)
ABSTRACT: The objective of our study was to evaluate the effect of altering the dietary supply of acetate, palmitic acid (PA), and cottonseed on the yields of milk components and milk fatty acids (FA) in lactating dairy cows. Thirty-two multiparous Holstein cows (133 ± 57 DIM, 50.5 ± 7.2 kg/d of milk) were used in a 4 × 4 Latin square split plot design with a 2 × 2 factorial arrangement of subplot treatments. Cows were blocked by ECM yield and allocated to a main plot receiving a basal diet (n = 16) with no supplemental PA (low PA) or a basal diet (n = 16) with 1.5% inclusion of a FA supplement containing ∼85% PA (high PA). In each main plot, the following subplots of treatment diets were fed in a Latin square arrangement consisting of 14-d periods: (1) a control diet (CON), (2) the control diet supplemented with 3% sodium acetate (AC), (3) the control diet supplemented with 12% whole cottonseed (CS), and (4) the control diet supplemented with 3% sodium acetate and 12% whole cottonseed (CS+AC). The PA supplement and sodium acetate replaced soyhulls, and whole cottonseed replaced cottonseed hulls and meal. All diets were balanced for 30% NDF, 23% forage NDF, 28% starch, and 17% CP. Sources of FA were classified as de novo (<16 carbons), mixed (16-carbon), and preformed (>16 carbons). The statistical model included the random effect of cow nested within basal diet and fixed effect of period, basal diet, acetate, cottonseed, and their interactions. Three-way interactions among basal diet, acetate, and cottonseed were observed for the yields of milk fat, 3.5% FCM, and the molar yields of de novo FA, mixed FA, and preformed FA. In the low PA diets, AC and CS+AC increased the yields of milk fat and FCM compared with CON and CS, whereas, in the high PA diets, CS+AC increased the yields of milk fat and FCM compared with the other treatments and AC increased milk fat yield compared with CON and CS. Compared with low PA, high PA increased milk fat content, mixed FA yield, and tended to increase C4:0 yield. Diets containing acetate increased DMI and the yields of milk fat, ECM, FCM, de novo FA, mixed FA, and preformed FA compared with diets without acetate. Diets containing cottonseed increased the yields of milk and preformed FA, tended to increase the yields of FCM and protein, and decreased DMI and the yields of de novo FA and mixed FA compared with diets without cottonseed. In summary, in high PA diets, the inclusion of acetate plus cottonseed increased milk fat yield compared with the other treatments. The CON diet in high PA increased milk fat yield to the same extent as AC and CS+AC in low PA suggesting PA is important for initiating milk TG synthesis. Balancing the supply of de novo FA substrates and preformed FA is important for increasing the synthesis of milk fat triglycerides and milk fat production.